2002
DOI: 10.1021/cm0200745
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Region, Crystal Growth, and Characterization of Rubidium Titanyl Phosphate Codoped with Niobium and Lanthanide Ions

Abstract: We studied the crystallization region of RbTiOPO4 (RTP) codoped with Nb and Ln (Ln = Er3+ or Yb3+), taking as basis a range of molar ratios of Rb2O−P2O5−TiO2. Significant differences in the critical concentration of Nb2O5 and Ln2O3 when we substituted TiO2 with these oxides where observed. These differences depended on the initial molar ratio of Rb2O−P2O5−TiO2 used in each case. The critical concentrations of the two lanthanides were also different; the critical concentration of Yb2O3 was lower than that of Er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…These include the difficulty in producing highgrade TiO 2 with tightly controlled physical properties and the fact that, in its basic form, it functions only under UV irradiation [23]. Many factors govern the physicalchemical properties of TiO 2 during its production such as the speed of growth, the diffusion coefficient, and the ionic radii [24]. The method of preparation and posttreatment conditions also play prominent roles in synthesizing a high efficiency TiO 2 product [25].…”
Section: Effects Of Dopants In the Formation Ofmentioning
confidence: 99%
“…These include the difficulty in producing highgrade TiO 2 with tightly controlled physical properties and the fact that, in its basic form, it functions only under UV irradiation [23]. Many factors govern the physicalchemical properties of TiO 2 during its production such as the speed of growth, the diffusion coefficient, and the ionic radii [24]. The method of preparation and posttreatment conditions also play prominent roles in synthesizing a high efficiency TiO 2 product [25].…”
Section: Effects Of Dopants In the Formation Ofmentioning
confidence: 99%
“…The crystal seed was rotated at an angular speed of 45 rpm to favor the homogenization of the solution of growth, and avoid the formation of flux inclusions in the crystals. Further details on the crystal growth procedure can be found elsewhere [17]. For the experiments, 1mm thick plate samples with their main faces perpendicular to the polar axis were cut and polished up to optical grade.…”
Section: Introductionmentioning
confidence: 99%
“…This family of materials crystallizes in the orthorhombic system. Recently, we have shown that the use of Nb 5þ as co-dopant in RTP allows us to obtain a high concentration of Ln 3þ doping on the basis of charge compensation [18,19].…”
Section: Introductionmentioning
confidence: 99%